PENGARUH PENERAPAN MEDIA TUTORIALAUTOCAD TERHADAP KREATIVITAS BELAJAR SISWA KELAS XI JURUSAN TKJ - Iistigna, Iistigna; Sakti, Hadi Gunawan (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2020)
The Purpose research to be achieved in this study were to determine The Effect of Auto CAD tutorial Towards Students’ Creativity class XI at SMKN 9 Mataram in the academic year 2018/2019. The method used in determining the subject of this research is used random sampling techniques because the number of students is 136, so in this study the number of samples taken was 34 students. The method used in obtaining the data of this study was the questionnaire main method, documentation and observation as supporti ng method, while the data analysis method used statistical analysis with the Chi-square formula. The results of the analysis obtained in this study are the calculated X2 of 28.624 and X2 table of 9,488. Thus, was 28,624 > 9,488. This is means that the alternative hypothesis which that there was The Effect of Auto CAD tutorial Towards Students’ Creativity class XI at SMKN 9 Mataram in the academic year 2018/2019 was accepted and the null Hypothesis that there is no The Effect of Auto CAD tutorial Towards Students’ Creativity class XI at SMKN 9 Mataram in the academic year 2018/2019 was rejected. The conclusion obtained in this study was that there was The Effect of Auto CAD tutorial Towards Students’ Creativity class XI at SMKN 9 Mataram in the academic year 2018/2019, which means the results of this study are significant with a t count of 28,624.